Executive profiles and performance of real estate services: Evidence of reverse causality from Europe. (November 2022) - Ricciotti, Francesco; Cristofaro, Matteo; Abatecola, Gianpaolo; Mari, Michela
Abstract: What executive profiles govern the industry of real estate services in Europe? Does heterogeneity emerge in these profiles if different industry sectors and/or geographical areas are considered? Ultimately, does this heterogeneity impact on their firms' performance? As a key component of the real estate value chain, real estate services are central to direct, properly support, and also guarantee the ex post sustainability of urban development projects. However, knowledge on what factors affect their performance is still absent. In light of this gap, in this study we draw on Upper Echelons Theory and analyze the socio-demographic features of key executives from a panel of listed European real estate service firms. We not only search for homogeneity/heterogeneity in these executives' profiles, but also for a potential connection with their firms' profitability. Results from our analysis show that, given their homogeneity, gender, age, and tenure do not apparently represent a catalyst for firm performance differential; in contrast, on the basis of their heterogeneity, advanced education and past industry experiences outside real estate can positively count. The theoretical contribution of our study, which proposes a model of inter-environment reverse causality, and implications for research and urban policy making are then presented. Highlights: Do executive profiles affect the performance of Real Estate Services (RES)? RES are key in urban projects, but knowledge on their performance drivers is scarce. We analyze 150 executive profiles from a panel of RES firms listed in Europe. Advanced education, and experiences outside real estate, support firm performance. A model of inter-environment reverse causality, and implications, follow.